Molecular understanding of the morphology and properties of lignin nanoparticles: unravelling the potential for tailored applications - Pylypchuk, Ievgen V; Karlsson, Maria; Lindén, Pär A; Lindström, Mikael E; Elder, Thomas; Sevastyanova, Olena; Lawoko, Martin (Green chemistry : an international journal and green chemistry resource : GC, 2023)
Studies have shown that the size of LNP depends on the molecular weight ( ) of lignin. There is however need for deeper understanding on the role of molecular structure on LNP formation and its properties, in order to build a solid foundation on structure-property relationships. In this study, we show, for similar lignins, that the size and morphology of LNPs depends on the molecular structure of the lignin macromolecule. More specifically, the molecular structure determined the molecular conformations, which in turn affects the inter-molecular assembly to yield size- and morphological-differences between LNPs. This was supported by density functional theory (DFT) modelling of representative structural motifs of three lignins sourced from Kraft and Organosolv processes. The obtained conformational differences are clearly explained by intra-molecular sandwich and/or T-shaped π-π stacking, the stacking type determined by the precise lignin structure. Moreover, the experimentally identified structures were detected in the superficial layer of LNPs in aqueous solution, confirming the theoretically predicted self-assembly patterns. The present work demonstrates that LNP properties can be molecularly tailored, consequently creating an avenue for tailored applications.